Structural and semantic organisation of retrospection in the prose of V. V. Gnilomedov - Digadyuk, Valentsina P. (Journal of the Belarusian State University. Philology, 2023)
The article presents the results of a study of the category of retrospection based on the material of V. Gnilomedov’s fiction; the features of its typification are determined based on the method of introducing a retrospective plan into the plot of the work. The methods of representation of compositional-textual retrospection are revealed such as information addition of facts, comparison of events, method of direct actualization of past events, cause-and-effect relations. Markers of the category of time are qualified and systematized, including lexical units of time, forms of participles, types of complex sentences, connective constructions, constructions with syntactic incompleteness and ellipsis, intertext inclusions. The peculiarity of the representation of textual plot retrospection is the realization of events in the same time space with retrospective excursions, the presence of the main retrospective storyline within the base time, as well as the retrospective interdependence between the novels-trilogies. The relevance of this topic is due to its belonging to the modern direction – the linguistics of the text, as well as the need for a comprehensive analysis of the category of retrospection in Belarusian linguistics. The results of the work done can be used in studying the problems of differentiation and interpretation of categories of literary text, in creating the grammar of the Belarusian language.